Representações dos profissionais no desenvolvimento da Política de Saúde Mental em Fortaleza: uma avaliação em processo no espaço do CAPS Geral da Secretaria Executiva Regional III - Coqueiro, Neusa Freire (2013)
The present study aimed to evaluate the social representations of professional performers mental health policy, aiming to grasp how they interpret this new model of care. We tried to uncover the meaning of mental health policy for professional Brazilian Center for Psychosocial Care (CAPS) in the city of Fortaleza. The analytical basis of this study is the foundational theory of social representations, which, according to Moscovici (2007), are specific phenomena that are related to a particular way of understanding and communicating. To understand the object, we developed a process evaluation, inspired by the dynamic investigative deeper evaluation. The locus of the research was CAPS Regional Executive Secretary General of III, which has an agreement with the Federal University of Ceará - UFC. To undertake this research in the field of process evaluation of public policy, we have developed a qualitative study, using a case study. This method proved to be suitable to thoroughly understand the process of social representations in the design of the CAPS professionals concerned. There was use of participant observation, semistructured interview with a tape recorder when allowed and field diary. The founding concepts of this research were: social representations, psychiatric reform, institutionalization, deinstitutionalization, normality and abnormality, identity and difference, traditional clinical and clinical enlarged. These concepts, found resonance in theoretical thinking of authors like Canguilhem (2000), Goffman (2008), Foucault (1993), Bourdieu (2007), Silva (2012), Amarante (2009), Fields (2003) among others. The data from this evaluation study were analyzed according to the method of content analysis, an approximation of the unblinding no apparent prospect of Bardin. Alternatively content analysis approach sought to formulate themes proposed by Mirian Limoeiro. Professionals had position on behalf of people with mental disorder, demonstrating aversion treatment asylum. They acknowledged the progress made in mental health policy in Fortaleza, however rigorously criticized the form of organization and operationalization of activities. Value the psychiatric deinstitutionalization as proposed humanization, citizenship and strengthen family and community bonds, but for most it is understood as synonymous with deinstitutionalization. Identified weaknesses in the system of mental health care, including: high level of care for the number of staff, disorderly closure of psychiatric hospitals, lack of places to stay in crisis. As a strategy to advance this policy suggested: broadening of CAPS, but seen as the main strategy of advancement, creating an open, due to the significant number of outsourced workers in these services and creation of psychiatric beds in general hospitals. Most showed superficial knowledge about the psychiatric reform and therapeutic interventions are still focused on a dimension of elimination of symptoms. Knowledge is sine qua non to be no change in thinking and acting. It is essential to adopt a comprehensive and well-designed continuing education on mental health issues important considering the repositioning of opinions towards the new model of mental health care.